2007
DOI: 10.1016/j.jneumeth.2007.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on brain oxygenation regulation during changes in position

Abstract: Introduction: Reports indicate that brain regulation of oxygenation is inhibited in patients with low baseline oxyhemoglobin concentrations and that brain oxyhemoglobin concentrations are decreased with aging. The purpose of this study was to determine if regulation of brain oxygenation to changes in blood pressure is inhibited by normal aging. Methods: Brain oxyhemoglobin (OHb) and deoxyhemoglobin (HHb) concentrations were determined from the forehead using a frequency domain near infrared spectroscopy in 27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Furthermore, NIRS is potentially useful to assess cerebral autoregulation (Steiner et al 2009 ; Kainerstorfer et al 2015 ). Previous studies investigated cerebral oxygenation responses using NIRS in healthy adults during head-up tilt (Houtman et al 1999 ; Krakow et al 2000 ; Kurihara et al 2003 ), compared responses to standing up or sitting up in younger and older adults (Kawaguchi et al 2001 ; Gatto et al 2007 ; Edlow et al 2010 ; Kim et al 2011 ), compared responses to standing up with and without calf muscle tensing (Kawaguchi et al 2001 ; van Lieshout et al 2001 ), or determined reproducibility of responses in older adults (Mehagnoul-Schipper et al 2001 ). These studies reported a cerebral oxygenation drop within 30 s after standing up.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NIRS is potentially useful to assess cerebral autoregulation (Steiner et al 2009 ; Kainerstorfer et al 2015 ). Previous studies investigated cerebral oxygenation responses using NIRS in healthy adults during head-up tilt (Houtman et al 1999 ; Krakow et al 2000 ; Kurihara et al 2003 ), compared responses to standing up or sitting up in younger and older adults (Kawaguchi et al 2001 ; Gatto et al 2007 ; Edlow et al 2010 ; Kim et al 2011 ), compared responses to standing up with and without calf muscle tensing (Kawaguchi et al 2001 ; van Lieshout et al 2001 ), or determined reproducibility of responses in older adults (Mehagnoul-Schipper et al 2001 ). These studies reported a cerebral oxygenation drop within 30 s after standing up.…”
Section: Introductionmentioning
confidence: 99%
“…Within infants, various studies have looked at the impact of several head and body positions on cerebral tissue oxygenation, either measured in the midline or bilaterally, and did not find any significant alterations in cerebral tissue oxygenation [23,24]. In 24 preterm infants, Ancora et al found that hemodynamic changes after postural variations depend on gestational age [15]. Head rotation in newborns with a gestational age < 26 weeks produced a reduction in normalized tissue hemoglobin index with stable tissue oxygenation index.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to infants, some significant results in adults were found. Various studies showed a significant decrease of cerebral tissue oxygenation in anesthetized patients when body position was changed from the supine to the sitting position [14,15,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-distance methods (see Section "Multi-Distance Methods") have been employed for absolute measurements of cerebral concentration and/or saturation of hemoglobin in newborn piglets (Fantini et al, 1999;Zhang et al, 2000), in rats (Culver et al, 2003), in newborn and infants (Franceschini et al, 2007;Grant et al, 2009;Roche-Labarbe et al, 2010Lin et al, 2013b, Lin T.-Y. et al, 2016Dehaes et al, 2014Dehaes et al, , 2015Demel et al, 2014bDemel et al, , 2015Farzam et al, 2017;Ferradal et al, 2017;Schwarz et al, 2018), and in adults under normal conditions (Fantini et al, 2003;Gatto et al, 2006Gatto et al, , 2007McIntosh et al, 2010;Hallacoglu et al, 2012Hallacoglu et al, , 2013Scholkmann et al, 2013a;Clancy et al, 2015;Kainerstorfer et al, 2015;Yang and Dunn, 2015;Moreau et al, 2016;Davies et al, 2017;Blaney et al, 2019;Pham et al, 2019), under anesthesia (Paisansathan et al, 2007;Meng et al, 2012a,b), hypoxia (Davies et al, 2017), pathological conditions such as multiple sclerosis (Yang and Dunn, 2015), stroke (Moreau et al, 2016), traumatic brain injury (Davies et al, 2019), before and during electro-convulsive therapy (ECT) (Fabbri et al, 2003), during neurovascular surgery …”
Section: Absolute Measurements With a Combination Of Intensity And Phmentioning
confidence: 99%